Multidrug resistance found in extended-spectrum beta-lactamase-producing Enterobacteriaceae from rural water reservoirs in Guantao, China - Zhang, Hongna; Zhou, Yufa; Guo, Shuyuan; Chang, Weishan (Frontiers in Microbiology, 2015)
Extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae have been isolated from humans and animals across the world. However, data on prevalence of ESBL-producing Enterobacteriaceae from rural water reservoirs is limited. This study aimed to isolate and characterize ESBL-producing Enterobacteriaceae in rural water reservoirs in Guantao, China. ESBL-producing Enterobacteriaceae were found in 5 (16.7％) of 30 sampled rural water reservoirs. 66 individual isolates expressing an ESBL phenotype were obtained in the present study. Species identification showed that 42 representatives of Escherichia coli, 17 Klebsiella pneumoniae, 4 Raoultella planticola, and 3 Enterobacter cloacae. 20 isolates contained a single bla gene, including CTX-M (17 strains), TEM (2 strains), and SHV (1 strain). 46 isolates contained more than one type of beta-lactamase genes. ESBL-producing Enterobacteriaceae isolated in this study were all multidrug resistant. These findings indicated that the seroius contamination of ESBL-producing Enterobacteriaceae in rural water resevoirs existed in Guantao, China.